Origin story, part one. - Stokel-Walker, Chris (New Scientist, 2025)
The article in New Scientist delves into the early life of Bill Gates, co-founder of Microsoft, as explored in his autobiography "Source Code: My beginnings." It highlights Gates' journey from a driven teenager in Seattle to the establishment of Microsoft with Paul Allen. The autobiography provides insights into Gates' upbringing, his drive to innovate in the tech industry, and the influences that shaped his success. While the book is well-researched and engaging, it ends just as Microsoft is taking off, leaving readers eager for the sequels to learn more about the evolution of the company.